Bone Augmentation with Simultaneous Implant Placement and Immediate Loading - Philippe, Van Camp (New Horizons in Medicine and Medical Research Vol. 10, 2022)
In this work we propose a protocol to treat edentulous patients in need of a bone graft in an expeditous but still reliable manner. We aim to evaluate the feasibility of simultaneous extractions, bone grafting, IPI placement and immediate loading in both jaws. After this first stage, the process is repeated with the placement of final dental implants with again an immediate loading protocol. This protocol was applied to an appropriate patient group at the Elisabeth Tweesteden Hospital (Tilburg, the Netherlands), followed up for at least 1 year. We conclude that although this is a complex procedure due to the intricate step-by-step process, the protocol shows good and predictable results with an implant survival at 100% and the success rate at 97%.